2005
DOI: 10.1353/cja.2005.0065
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Restorative Care Education and Training Program for Nursing Homes

Abstract: RÉSUMÉLes soins de rétablissement visent à rompre le cycle de la dépendance et du déclin fonctionnel dans les maisons de soins infirmiers en répondant aux besoins particuliers des divers résidents. Le programme RCET (Restorative Care Education and Training) comprend un atelier de cinq semaines ainsi qu'un manuel d'information destiné autant aux superviseurs qu'aux prestataires de soins directs. Ce document décrit l'approche du programme RCET et présente la mise en oeuvre, les procédés et les résultats d'une év… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 31 publications
(75 reference statements)
0
20
0
Order By: Relevance
“…Ten studies focused on changing the philosophy or aspects of care culture, such as person-centered care, emotion-oriented care, awareness oriented care and restorative care [ 86 103 ](see Table 11 ). One study offered training only [ 91 ], and one changed staff responsibilities and care procedures [ 93 ]. The remaining studies combined training with other intervention components such as mentoring or support [ 86 , 87 , 89 , 92 , 97 , 99 , 100 , 102 ] and audit and feedback [ 86 , 89 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten studies focused on changing the philosophy or aspects of care culture, such as person-centered care, emotion-oriented care, awareness oriented care and restorative care [ 86 103 ](see Table 11 ). One study offered training only [ 91 ], and one changed staff responsibilities and care procedures [ 93 ]. The remaining studies combined training with other intervention components such as mentoring or support [ 86 , 87 , 89 , 92 , 97 , 99 , 100 , 102 ] and audit and feedback [ 86 , 89 ].…”
Section: Resultsmentioning
confidence: 99%
“…Seven out of eight studies that measured whether staff changed their behavior showed at least some improvements [ 86 , 90 , 91 , 94 , 96 , 98 , 101 ]. There did not appear to be a pattern in the intervention components that produced successful interventions.…”
Section: Resultsmentioning
confidence: 99%
“…Originally designed with rehabilitation populations in mind [57], the reliability and validity of the FIM has been assessed with older adults in acute care [59] and the community [58,60] with demonstrated reliability in each of these settings [61]. More recently the FIM has been used in a LTC setting [21,62,63] and has been compared with the Resident Assessment Instrument [64-68]. Eight responsiveness studies all found the physical but not the cognitive subscales to be responsive to change [59,65].…”
Section: Methodsmentioning
confidence: 99%
“…Most of the studies included single sites or were quasiexperimental. [21][22][23][24] There have been a few randomized trials that have addressed restorative care activities. [25][26][27] These studies focused on morning care activities in residents with cognitive and behavioral problems, and the findings indicated that, with appropriate cues and nursing care, individuals with significant cognitive impairment could increase function with regard to morning care activities.…”
mentioning
confidence: 99%